Comparative Evaluation of the Inhibitory Effect of Some Essential Oils with Antibiotics against Pseudomonas aeruginosa. (1st October 2014) - El-Hosseiny, Lobna; El-Shenawy, Moustafa; Haroun, Medhat; Abdullah, Fadhil
Abstract : Gas chromatography/mass spectroscopy analysis was performed to identify the chemical components of three extracted essential oils including thyme, marjoram, and sage. The antibacterial activity of the extracted essential oils against Pseudomonas aeruginosa (ATCC 9027) was investigated using disc diffusion assay, either alone or in combination with standard antibiotics (piperacillin, cefepime, meropenem, gentamicin, and norfloxacin). Results showed that the studied oils exhibited a variety of activities against the tested bacterium. Thyme oil was the most active followed by marjoram oil, whereas sage displayed no activity towards the tested organism. Thyme oil enhanced the antibacterial activity of cell wall targeting antibiotics (piperacillin, cefepime, and meropenem) by more than twofold. Marjoram oil potentiated the activity of all the tested antibiotics except norfloxacin. Sage, despite its inactivity against pseudomonas, synergistically enhanced the activity of piperacillin, meropenem, and gentamicin. Thyme essential oil, containing thymol as a major component (33.6%), exhibited higher activity alone or in combination with antibiotics than marjoram which contained alcoholic terpenes or sage essential oil that contained 1, 8-cineole as its major component (29%). The investigated oils, as natural bioactive agents, may be used to enhance the activity of antibiotics towards pseudomonas .